Elevated heat shock proteins in bipolar disorder patients with hypothalamic pituitary adrenal axis dysfunction. Issue 27 (July 2018) - Cheng, Yuhang; Li, Zhili; He, San; Tian, Yujie; He, Fan; Li, Wenbiao
Abstract: Background: Heat shock proteins( HSP) might be useful as biomarkers for bipolar disorder (BD) which would be clinically valuable since no reliable biomarker for BD has so far been identified. The purpose of this study was to assess the heat shock proteins CPN10, CPN60, and CPN70 as potential biomarkers of BD. Methods: The study included 100 BD patients recruited from a hospital during 2012 and 2013. The study also included 94 healthy controls. Among the BD patients, 33 had abnormal hypothalamic-pituitary-adrenal (HPA) axis activity. Blood samples were obtained from the patients and controls. The chemiluminescence method, mass spectrometry, and flow cytometry were used for analysis. Results: The BD patients compared with the controls had a significantly lower level of CPN10 and significantly higher levels of CPN60 and CPN70. The BD patients with abnormal HPA axis activity had a significantly lower level of CPN60 compared with the normal HPA axis activity group of BD patients. The CPN60 level significantly inversely correlated with adrenocorticotropic hormone (ACTH) level in patients with bipolar depression and in patients with bipolar hypomania, and CPN70 significantly correlated with ACTH level in patients with bipolar depression and hypomania. Conclusions: Our findings suggest that the heat shock proteins CPN10, CPN60, and CPN70 might have potential as biomarkers for BD and CPN60 blood level might distinguish patients with abnormal HPA axis activity from those with normal HPA axis activity. Abstract : Supplemental Digital Content is available in the text